2007
DOI: 10.2319/0003-3219(2007)077[0505:teomts]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Modifying the Self-etchant Bonding Protocol on the Shear Bond Strength of Orthodontic Brackets

Abstract: Only one light curing application is needed to successfully bond brackets when using SEPs and adhesives. This approach can potentially reduce technique sensitivity as well as chair time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
2
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 22 publications
2
87
2
6
Order By: Relevance
“…With regard to ARI, a previous study 21 demonstrated that TSEP presented all the adhesive remained on the tooth and another study reported that more than 90% of the adhesive remained on the tooth, 30 corroborating the present study, which showed most of the Transbond TM Plus Color Change specimens with over 50% of the adhesive on enamel. On the other hand, the two-step agents presented less than 50% of the adhesive on enamel.…”
Section: Discussionsupporting
confidence: 80%
“…With regard to ARI, a previous study 21 demonstrated that TSEP presented all the adhesive remained on the tooth and another study reported that more than 90% of the adhesive remained on the tooth, 30 corroborating the present study, which showed most of the Transbond TM Plus Color Change specimens with over 50% of the adhesive on enamel. On the other hand, the two-step agents presented less than 50% of the adhesive on enamel.…”
Section: Discussionsupporting
confidence: 80%
“…Although designed for use in operative bonding procedures, SEPs/adhesives have been used to successfully bond orthodontic brackets with shear bond strength (SBS) values similar to those for the conventional acid-etch technique. 4,5 Transbond Plus Self-Etching Primer (TPSEP; 3M Unitek, Monrovia, Calif) is a dental adhesive system developed for orthodontic bonding. The TPSEP system has three compartments.…”
Section: Introductionmentioning
confidence: 99%
“…14 Although marketed for use in operative dentistry, it has been demonstrated that other restorative-based selfetching systems have been used successfully to bond orthodontic brackets. 12,13 Unlike most self-etching systems, the AdheSE One offers the advantage of not having to be mixed prior to application. This in turn may reduce technique sensitivity by eliminating the chance of improper mixing and the resulting inadequate SEP activation.…”
Section: Introductionmentioning
confidence: 99%
“…12 Additionally, it was observed that when using a self-etching adhesive to bond brackets, no significant difference was seen when the SEP was cured either in separate steps or simultaneously with the bonding adhesive. 13 A new self-etching adhesive, AdheSE One (Ivoclar Vivadent Inc, Amherst, NY), was introduced for use in operative dentistry. In a recent study, this self-etching adhesive provided microtensile bond strengths to enamel that were similar to those of three other selfetching adhesives currently available on the market.…”
Section: Introductionmentioning
confidence: 99%